Financial Feasibility Analysis of Small and Medium Business Development CV. XYZ in Madiun East Java - Ma'ruf Pambudi Nurwantara; Sapta Raharja; Faqih Udin (SEAS (Sustainable Environment Agricultural Science), 2017)
Abstract The agricultural sector is the leading sector of the Indonesian economy. Oyster mushrooms are one of the subsectors of agriculture. High opportunities for business sustainability and consumer demand make it necessary to analyze the financial viability of this venture. Financial feasibility analysis is required to assist CV. XYZ to see the feasibility of the development effort to be run. This research uses investment and production cost analysis method, cost of goods sold, Break Even Point (BEP), Net Present Value (NPV), Payback Period (PP), and Incremental Rate of Return and Ratio B/C. The result of the financial feasibility of CV. XYZ is BEP by selling product 50 baglog or Rp. 150,000 per production. NPV valued at Rp 253,181,432, Payback Period in year 1, IRR worth 40% and Ratio B/C 1.42 in the first year up to the fifth year. Keywords: Financial feasibility,business development, oyster mushrooms